FRI0402 Microrna-125b regulates apoptosis in systemic sclerosis. (12th June 2018) - Kozlova, A.; Pachera, E.; Maurer, B.; Jüngel, A.; Distler, J.H.; Kania, G.; Distler, O.
Abstract : Background: The role of apoptosis in systemic sclerosis (SSc) is an emerging topic. MicroRNAs (miRs) are a class of small noncoding RNAs that regulate many important biological processes including apoptosis. Objectives: To analyse the differential expression, regulation and pathophysiological role of miR-125b in systemic sclerosis. Methods: MiR-125b expression was assessed by qPCR on RNA derived from cultured fibroblasts, whole skin biopsies and paraffin embedded dermis and epidermis from healthy controls (HC) and SSc patients. Fibroblasts were stimulated with pro-inflammatory and/or pro-fibrotic cytokines and with different epigenetic stimuli. Knockdown with anti-miR-125b (or scrambled controls) in HC fibroblasts was performed to identify downstream effects. RNA from healthy fibroblasts (n=4) after knockdown was proceeded to RNAseq using Illumina HiSeq2000. Bioinformatics analysis included differential gene expression and pathway analysis. Sequencing data were validated using qPCR (on HC and SSc fibroblasts). Apoptosis was assessed by Caspase-Glo 3/7 assay, Western Blot of cleaved caspase 3 and Annexin V live assay on cultured fibroblasts. Results: MiR-125b was downregulated in SSc skin biopsies (n=10, median 47%, Q1, 3 35%, 69%; p<0.01) in comparison with HC skin (n=10). To localise its expression in the skin, we separately analysed miR-125b expression in dermis and epidermis of paraffin embedded skin where it was downregulated in both compartments (n=3 each). The expression of miR-125b in primary dermal fibroblasts was also downregulated (median 53%, Q1, 3 36%, 58%; n=10, p<0.01) compared to HC fibroblasts (n=10). MiR-125b expression was not affected by major cytokines operative in SSc such as TGFβ or PDGF. However, TSA (histone deacetylase pan-inhibitor) downregulated miR-125b expression in a time- and dose-dependent manner (n=5, median 23%, Q1, 3 19%, 48%; p<0.01). RNAseq identified >3500 differentially expressed genes with p<0.05. More than half of the differentially expressed genes with at least 15% change were predicted targets of miR-125b by TargetScan and MiRWalk, indicating successful functional inhibition of miR-125b. Gene ontology revealed apoptosis regulation as the main activated pathway. Apoptotic genes included BAK1, BMF and BBC3, which are part of the BCL2 apoptosis pathway and predicted targets of miR-125b. Consistent with the sequencing results, qPCR confirmed that miR-125b knockdown upregulated these genes 24, 48 and 72 hours after transfection (n=12, p<0.01 for each). BAK1 showed the strongest induction, that was also confirmed on the protein level by Western blot. Accordingly, miR-125b knockdown resulted in an increased apoptosis (at least 1.5-fold, n=10, p<0.01) compared to scrambled controls, measured by Caspase-Glo 3/7 assay 24, 48 or 72 hours post-transfection. Consistently, miR-125b overexpression decreased apoptosis (by at least 50%, n=10, p<0.01) at these time points. Cleaved caspase 3 was upregulated in anti-miR-125b transfected cells (median 2.3 fold, Q1, 3 1.6, 4; n=10, p<0.01) confirmed by Western Blot. Annexin V live assay showed prevailing of apoptosis after miR-125b downregulation. Conclusions: MiR-125b is downregulated in SSc skin and primary SSc dermal fibroblasts. MiR-125b downregulation increases apoptosis in dermal fibroblasts that might be a compensatory strategy against excessive fibrosis that could be used for therapeutic purposes. Disclosure of Interest: A. Kozlova: None declared, E. Pachera: None declared, B. Maurer Grant/research support from: AbbVie, Protagen, EMDO, Novartis, German SSc Society, OPO foundation, congress support from Pfizer, Roche, Actelion. MSD. Patent licensed: mir-29 for the treatment of systemic sclerosis, A. Jüngel: None declared, J. Distler Shareholder of: 4D Science, Grant/research support from: Anamar, Active Biotech, Array Biopharma, BMS, Bayer Pharma, Boehringer Ingelheim, Celgene, GSK, Novartis, Sanofi-Aventis, UCB, Consultant for: Actelion, Active Biotech, Anamar, Bayer Pharma, Boehringer Ingelheim, Celgene, Galapagos, GSK, Inventiva, JB Therapeutics, Medac, Pfizer, RuiYi and UCB, G. Kania Grant/research support from: Bayer Pharma AG, Germany; conference support: Actelion, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, Mitsubishi Tanabe Pharma and Roche; patent mir-29 for the treatment of systemic sclerosis licensed, Consultant for: Actelion, Bayer, BiogenIdec, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa and UCB